MRI-detected knee ligament sprains and associated internal derangement in athletes competing at the Rio de Janeiro 2016 Summer Olympics - Kompel, A.; Haran, P. H.; Murakami, A. M.; Engebretsen, L.; Jarraya, M.; Roemer, F.; Guermazi, A. (Open Access Journal of Sports Medicine, 2021)
Purpose: Describe the frequency and severity of knee ligament sprains diagnosed by MRI in athletes participating at the 2016 Summer Olympic Games, their association with certain sports and assess correlations with additional knee structural injury. Patients and Methods: All knee MRIs performed in the Olympic Village and polyclinics during the 2016 Olympics were retrospectively, blindly reviewed for ligament sprains and associated knee injuries. In addition to the absence or presence of these abnormalities, athletes were stratified by age, gender and sport. Results: 11,274 athletes participated in the 2016 Olympic Games: 113 athletes received at least one knee MRI with some having bilateral or repeat MRI on the same knee. Anterior cruciate and medial collateral ligament (ACL/MCL) sprains were most common, accounting for 32 of the 43 sprains (74.4%). Wrestling (10), hockey (7), athletics (7), and judo (5) accounted for over half of ligament sprains. ACL sprains showed a significant positive correlation with medial, lateral meniscal tears and bone contusions. The positive correlation between posterior cruciate ligament (PCL) sprains with MCL/lateral collateral ligament sprain, and popliteus tendon tear was statistically significant with 50% of total PCL sprains occurring in hockey. When athletes were stratified by gender, ligament sprains had a similar occurrence and distribution between men and women. Conclusion: Knee ligament sprains, at the Rio 2016 Games, were most common in wrestling, hockey, athletics and judo with ACL and MCL sprains most frequent. Meniscal tears and bone contusions occurred often with ACL sprains. PCL sprains tended to be multi-ligamentous injuries. Sustained ligament sprains had similar occurrence between genders, while men had a peak incidence of sprains at a younger age and women at an older age.